Establishment and experimental validation of a novel cuproptosis-related gene signature for prognostic implication in cholangiocarcinoma - Chen, Jialu; Yu, Xiaopeng; Tong, Huanjun; Tang, Chengwei; Tang, Zhaohui (Frontiers in Oncology, 2022)
Background Cholangiocarcinoma (CCA) is a highly malignant, heterogeneous bile duct malignancy with poor treatment options. A novel type of cell death termed cuproptosis was recently demonstrated to closely correlate with tumor progression. To gain more insight into the role of cuproptosis in CCA, we investigated the prognostic implications of cuproptosis related genes (CRGs) and their relationship to the development of CCA. Methods Gene expression data for CCA were obtained from the European Bioinformatics Institute (EMBL-EBI) database. Least absolute shrinkage and selection operator (LASSO) penalized Cox regression was used to construct a prognostic risk model based on CRGs. RNA-seq, qRT−PCR and immunohistochemistry staining were used to verify the expression of CRGs in human CCA tissues or cell lines. Further in vitro experiments were performed to demonstrate the role of cuproptosis in CCA. Results We established a 4-gene signature (ATP7A, FDX1, DBT and LIAS) that exhibited good stability and was an independent prognostic factor for CCA. Seventy-five CCA samples were divided into high- and low-risk groups based on the risk score. Enrichment analysis revealed increased extracellular activity in the high-risk group and increased lipid metabolic activity in the low-risk group. Moreover, the 4 signature genes were verified in clinical samples and cell lines by RNA-seq, qRT−PCR and immunohistochemistry. Further experiments confirmed that cuproptosis can significantly inhibit the viability of CCA cells. Knockdown of the key gene LIAS ameliorated the toxicity of cuproptosis to CCA cells. Conclusion We established a 4-gene prognostic signature based on cuproptosis and explored the role of cuproptosis in CCA. The results provide an effective indicator for predicting the prognosis of cuproptosis in CCA.